Nationwide survey on resource availability for implementing current sepsis guidelines in Mongolia - Bataar Otgon; Ganbold Lundeg; Ganbat Tsenddorj; Stefan Jochberger; Wilhelm Grander; Inipavudu Baelani; Iain Wilson; Tim Baker; Martin W Dünser (The World Health Organization, 2010)
OBJECTIVE: To assess if secondary and tertiary hospitals in Mongolia have the resources needed to implement the 2008 Surviving Sepsis Campaign (SSC) guidelines. METHODS: To obtain key informant responses, we conducted a nationwide survey by sending a 74-item questionnaire to head physicians of the intensive care unit or department for emergency and critically ill patients of 44 secondary and tertiary hospitals in Mongolia. The questionnaire inquired about the availability of the hospital facilities, equipment, drugs and disposable materials required to implement the SSC guidelines. Descriptive methods were used for statistical analysis. Comparisons between central and peripheral hospitals were performed using non-parametric tests. FINDINGS: The response rate was 86.4% (38/44). No Mongolian hospital had the resources required to consistently implement the SSC guidelines. The median percentage of implementable recommendations and suggestions combined was 52.8% (interquartile range, IQR: 45.8-67.4%); of implementable recommendations only, 68% (IQR: 58.0-80.5%) and of implementable suggestions only, 43.5% (IQR: 34.8-57.6%). These percentages did not differ between hospitals located in the capital city and those located in rural areas. CONCLUSION: The results of this study strongly suggest that the most recent SSC guidelines cannot be implemented in Mongolia due to a dramatic shortage of the required hospital facilities, equipment, drugs and disposable materials. Further studies are needed on current awareness of the problem, development of national reporting systems and guidelines for sepsis care in Mongolia, as well as on the quality of diagnosis and treatment and of the training of health-care professionals.